The inhibitory potential of three scorpion venom peptides against multidrug-resistant Klebsiella pnemoniae - Giugliano, Rosa; Della Marca, Roberta; Chianese, Annalisa; Monti, Alessandra; Donadio, Federica; Esposito, Emanuela; Doti, Nunzianna; Zannella, Carla; Galdiero, Massimiliano; De Filippis, Anna (Frontiers in Microbiology, 2025)
BackgroundThe rise of drug-resistant bacterial infections, particularly those caused by Klebsiella pneumoniae underscores the urgent need for novel therapeutic candidates. Hospital-acquired infections from K. pneumoniae carbapenemase (KPC)-producing bacteria pose a serious health threat, particularly impacting the respiratory and urinary tracts. This study investigates the antibacterial efficacy of three antimicrobial peptides, called pantinins, derived from Pandinus imperator scorpions’ venom against K. pneumoniae and various KPC-producing clinical isolates.MethodsNon-toxic concentrations were established for each peptide using MTT method. Antibacterial activity was performed through the liquid microdilution assay to assess the minimum inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC). A time-kill test was conducted by recording the colonies forming units (CFUs) at several times and compared with those of the untreated bacteria. Finally, the effect of peptides on the gene expression of virulence factors of K. pneumoniae was evaluated through qPCR.ResultsAntibacterial assays demonstrated bactericidal effects for pantinin-1 and pantinin-2 within 1 h, while pantinin-3 displayed bacteriostatic properties. Noteworthy, MIC values ranged from 6 to 25 μM for K. pneumoniae and from 25 to 50 μM for KPC strains. Pantinins exert their antimicrobial effect through a membranolytic mechanism, directly interacting with outer membrane lipopolysaccharides (LPS), as evidenced by circular dichroism (CD) spectra and scanning electron microscopy (SEM). In addition, qPCR showed a reduction in virulence genes expression, suggesting the antibacterial effect of peptides also at transcriptional level.ConclusionThese findings support pantinins as promising candidates for treating multidrug-resistant K. pneumoniae infections.